Lead Identification from the Phytoconstituents of Cadaba fruticosa (L.) Druce for the Treatment of PCOS: A Computational Approach - Amudha, M.; Rani, S.; Parasuraman, P. (Current Overview on Pharmaceutical Science Vol. 1, 2022)
The purpose of these computational molecular docking experiments is to examine the efficacy of phytocomponents from Cadaba fruticosa (L.) Druce against CYP17. Hyperinsulinemia, monthly abnormalities, chronic metabolic disturbances, and hyperandrogenism are the hallmarks of polycystic ovary syndrome (PCOS). The enzyme CYP17 (P450c17) stimulates androgen production in the adrenal glands and ovaries. The major cause of hyperandrogenism is an increase in the activity of this enzyme. Ovarian theca cells can be protected from producing too much androgen by blocking the enzyme activity responsible for this process. The ethanolic extract of C. fruticosa's aerial parts has been analyzed by GC-MS, and it contains twenty different chemicals, according to the published literature. Using Schrodinger Glide software, the reported twenty compounds were subjected to a molecular docking investigation against CYP17. These findings were compared to the docked score of the reproductive medication clomiphene citrate. An inhibition range of -3.3 to -7.9 was observed across all 20 drugs. The docking scores of -7.9 and -6.8 for androstan-3-one and 17-hydroxy-2, 4-dimethyl and 3-trifluoroacetoxypentadecane, respectively, indicate potent inhibition. The findings showed that chemicals in C. fruticosa may inhibit the activity of an enzyme CYP17. The experimental methods used to identify the innovative medicine for infertility are illuminated by this research.